Facile green synthesis of Fe3O4 nanoparticles using aqueous leaf extract of Zanthoxylum armatum DC. for efficient adsorption of methylene blue. Issue 2 (3rd April 2018) - Ramesh, A. V.; Rama Devi, Dharmasoth; Mohan Botsa, Satish; Basavaiah, K.
ABSTRACT: We report a facile and green route for the synthesis of superparamagnetic magnetite nanoparticles (Fe3 O4 NPs) using aqueous leaf extract of Zanthoxylum armatum DC. for efficient adsorption of organic pollutant, methylene blue (MB). The phytochemicals present in the aqueous leaf extract Zanthoxylum armatum DC. are not only responsible for the formation of Fe3 O4 NPs, but also act as capping agent for Fe3 O4 NPs. The formation of Fe3 O4 NPs was confirmed by a range of spectroscopy and microscopy techniques such as UV–visible spectroscopy, Fourier transform infrared spectroscopy, powder X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and vibrating sample magnetometer. The spectroscopic results indicated the successful formation of Fe3 O4 NPs. FE-SEM and TEM images revealed the spherical shape with particle size of 17 nm. Fe3 O4 NPs showed superparamagnetism. Green synthesized Fe3 O4 NPs shows enhanced adsorption efficiency toward MB from contaminated water. The kinetic data of adsorption fitted very well with the pseudo-second order. The adsorption isotherm data fitted well to Langmuir isotherm and it was found to be 10.4712 mg/g adsorption capacity and it implies that the chemisorptions of MB on to Fe3 O4 NPs.